Training injuries in professional rugby reague - Gabbett, T. J.; Godbolt, R. J. B. (The Journal of Strength and Conditioning Research, 2010)
This study investigated the incidence of training injuries in professional rugby league players and identified the training activities that were associated with the highest rates of injury in these athletes. The incidence of training injuries was prospectively studied in 35 professional rugby league players (mean ± SD age 23.7 ± 3.8 years) over an entire season. Injury data were collected from 216 training sessions, which included all strength, conditioning, and game-based training sessions. During the season, a total of 126 training injuries were recorded, giving an overall incidence of injury of 20.7 per 1,000 training hours. The thigh was the most common site of injury, with twice as many posterior thigh injuries (19.8%) as anterior thigh injuries (9.5%). Hematomas (31.8%) and muscular strains (22.2%) were the most common types of injury. The majority of injuries (35.7%) were sustained in traditional conditioning activities that involved no skill component (i.e., running without the ball). In contrast, the incidence of injuries sustained while participating in strength (7.1%) and game-based training activities (14.3%) was low. Of the injuries that resulted in lost training time, one-third were sustained in traditional conditioning activities. Given the low incidence of injury in game-based activities, and the added skill and physical benefits associated with this form of training, strength and conditioning coaches should consider using appropriately designed game-based training activities as a physical conditioning tool in professional rugby league players.